Reducing organizational politics in performance appraisal: the role of coaching leaders in appraising age-diverse employees - Dello Russo, S. (2018)
We examined whether a supervisor’s coaching leadership style predicts the perception of organizational politics in performance appraisal (OPPA) reported by the collaborators. Additionally, we drew on social cognition and motivational lifespan development theories to hypothesize age-related differences in perceived OPPA and its link with the coaching leadership style. Using hierarchical linear modeling (HLM) on a sample of 576 employees and 112 leaders, we found that coaching leaders are perceived as less manipulative in their performance ratings, especially by older employees. This paper includes a discussion of the implications these results have for performance management of an age-diverse workforce.